Exploring the experiences and psychosocial stresses of Taiwanese patients with pulmonary hypertension: a qualitative interview study. (1st September 2018) - Chiang, Yung‐Chih; Hu, Li‐Yu; Couper, Jeremy; Cheng, Chin‐Chang; Wang, Ling‐Hsiang; Huang, Wei‐Chun; Lu, Ti
Abstract : About half of all patients with pulmonary hypertension (PH) experience psychological and emotional disturbances that affect their quality of life (QOL). There is a lack of studies exploring how psychiatric professionals can provide specific and effective mental health treatment to patients with PH. This study aimed to explore and understand the treatment experiences of patients with PH in Taiwan. We employed an exploratory qualitative design involving interviews with 17 patients with PH who were treated at Kaohsiung Veterans General Hospital in Taiwan. Participants were interviewed by a psychiatrist; the interviews were audiotaped and transcribed for thematic analysis by two researchers. We corroborate earlier findings showing that patients who have the rare disease PH often experience psychological or emotional disturbances throughout the treatment process. This study explored a model for psychiatric intervention based on patients' experience of having PH. We find that assessing and strengthening links to external resources can enhance patients' long‐term coping abilities, and thereby help reduce their psychological and emotional disturbances and improve their QOL.